Prognostic impact of p53 and/or NY‐ESO‐1 autoantibody induction in patients with gastroenterological cancers. Issue 3 (25th March 2020) - Hoshino, Isamu; Nabeya, Yoshihiro; Takiguchi, Nobuhiro; Gunji, Hisashi; Ishige, Fumitaka; Iwatate, Yosuke; Shiratori, Fumiaki; Yajima, Satoshi; Okada, Rei; Shimada, Hideaki
Abstract: Background and Aim: We evaluated the clinicopathological and prognostic significance of serum p53 (s‐p53‐Abs) and serum NY‐ESO‐1 autoantibodies (s‐NY‐ESO‐1‐Abs) in esophageal squamous cell carcinoma (ESCC), gastric cancer and hepatocellular carcinoma (HCC). Patients and Methods: A total of 377 patients, 85 patients with ESCC, 248 patients with gastric cancer, and 44 patients with HCC were enrolled to measure s‐p53‐Abs and s‐NY‐ESO‐1‐Abs titers by the enzyme‐linked immunosorbent assay before treatment. The clinicopathological significance and prognostic impact of the presence of autoantibodies were evaluated. Expression data based on the Cancer Genome Atlas and the prognostic impact of gene expression was also examined for discussion. Results: The positive rates of s‐p53‐Abs were 32.9% in ESCC, 15% in gastric cancer, and 4.5% in HCC. The positive rates of s‐NY‐ESO‐1‐Abs were 29.4% in ESCC, 9.7% in gastric cancer, and 13.6% in HCC. The presence of s‐p53‐Abs was not associated with tumor progression in these three cancer types. On the other hand, the presence of s‐NY‐ESO‐1‐Abs was significantly associated with tumor progression in ESCC and gastric cancer. The presence of s‐p53‐Abs and/or s‐NY‐ESO‐1‐Abs was significantly associated with poor prognosis in gastric cancer but not in ESCC nor HCC. Conclusions: The presence of s‐p53‐Abs and/or s‐NY‐ESO‐1‐Abs was associated with tumor progression in ESCC and gastric cancer. These autoantibodies might have poor prognostic impacts on gastric cancer (UMIN000014530). Abstract : NY‐ESO‐1 antibodies were significantly associated with tumor progression in gastric cancer and esophageal squamous cell carcinoma, while the presence of p53 and/or NY‐ESO‐1 antibodies was significantly associated with poor prognosis only in gastric cancer.